Forest structure and tree species composition of the understory of two central Amazonian várzea forests of contrasting flood heights - de Assis, Rafael Leandro; Wittmann, Florian (Flora. Morphologie, Geobotanik, Oekophysiologie, 2011)
We investigated species composition, distribution, and forest structure of understory trees (≥1m height, <10cm diameter at breast height) in two late-successional várzea forests subject to contrasting levels of inundation within the Mamirauá Sustainable Development Reserve, western Brazilian Amazon, and compared it with the overstory flora at the same study sites. In total, 1486 individuals and 116 woody species were recorded on an area totaling 3140m2. Individual densities and tree species richness were considerably higher in the high várzea than in the low várzea, which suggests that the heights and durations of the annual inundations are the main factor limiting species regeneration. In addition, approximately one third of the recorded species with densities ≥8 individuals showed regular or random spatial distribution patterns, which suggests that floodwaters act on dispersal strategies and species establishment. Independent of the forest type, floristic similarity between the understory and the overstory amounted to approximately 35%, and to approximately 10% when compared to other understory inventories in Amazonian várzea. Although the inventoried area of the understory amounted to only 16% of that of the overstory, species richness accounted for approximately 52–56% of that of the overstory. The results indicate that the understory flora of várzea forests is distinct and that it significantly increases local tree species richness. The understory flora of várzea forests therefore should be addressed in floristic inventories that provide the basis for regional and/or basin-wide estimations of tree diversity.